Swatting Flies for Health: Children and Tuberculosis in Early Twentieth-Century Montreal - Minnett, Valerie; Poutanen, Mary-Anne (Urban History Review / Revue d'histoire urbaine, 2007)
Responding to an appeal by city physicians and health reformers to destroy a prodigious disease carrier, the housefly, the Montreal Daily Star launched an island-wide contest in July 1912, offering prizes to children who collected the most dead flies. Nearly a thousand children, largely from working-class families, participated in a three-week-long "Swat the Fly" competition. Engaging Montreal children in this contest underscores a popular idea at the time that the best way to improve public health and combat the ignorance of a generation was to arm a new one with knowledge. While historians recognize that children's participation in campaigns to promote public health measures was pivotal to their success, youngsters are often rendered as passive recipients of reformers' efforts. We argue the contrary: children were active agents in public health crusades both as consumers and as advocates.